Corneal fibrosarcoma in a cat. (3rd February 2016) - Strong, Travis D.; Tangeman, Sarah; Ben‐Shlomo, Gil; Haynes, Joseph; Allbaugh, Rachel A.
Abstract: Purpose: To present the clinicopathologic features of a Domestic Short‐haired cat with spontaneous, intermediate‐grade corneal fibrosarcoma, possibly secondary to chronic corneal irritation associated with a corneal sequestrum. Methods: A 12‐year‐old, spayed female Domestic Short‐haired cat was evaluated for a slowly growing, pink, exophytic mass affecting the left cornea. The cat had presented 6 years previously for bilateral brown corneal sequestra, as well as 3 years previously for a small pale growth on the left cornea hypothesized to be an epithelial inclusion cyst and a corneal ulcer affecting the right eye. Incisional biopsy of the corneal mass indicated intermediate‐grade corneal fibrosarcoma within the corneal stroma. Owing to the potential for malignant behavior, the left globe was enucleated. Routine systemic staging was performed prior to surgery with no evidence of metastasis. Results: Definitive diagnosis of corneal fibrosarcoma was made through histopathologic examination of the incisional biopsy. There was an elevated mitotic index, indicating an intermediate‐grade phenotype. Histopathology of the enucleated globe substantiated the initial findings, and complete tumor resection was confirmed. Subjacent to the corneal fibrosarcoma, there was a region of necrotic tissue suggestive of a corneal sequestrum. Six months after diagnosis and enucleation, the patient remained healthy with no signs of local spread or distant metastasis. Conclusions: To the authors' knowledge, this is the first documented case of a corneal fibrosarcoma in a cat.